Bar deposition in glacial outburst floods: scaling, post-flood reworking, and implications for the geomorphological and sedimentary record - Marren, Philip M. (Géomorphologie : relief, processus, environnement, 2016)
The appearance of a flood deposit in the geomorphological and sedimentary record is a product of the both the processes operating during the flood, and those that occur afterwards and overprinting the deposit with a record of ‘normal’ processes. Nearly half of the total discharge of the November 1996 jökulhlaup on Skeiðarársandur was discharged through the Skeiðará river. The flood deposits have been extensively reworked since, up until 2009 when the channel was abandoned, effectively leaving the Skeiðará as a terrace, when retreat of Skeiðarárjökull directed meltwater to the adjacent Gígjukvísl river system. This paper describes the creation and modification of jökulhlaup barforms in the Skeiðará river, relating the changes to post-flood fluvial processes and glacier retreat. Large compound bars formed from the amalgamation of unit bars up to 1.5 km long. The location of the compound bars was governed by the macro-scale topography of the flood channel, and their size by upstream channel width in accordance with bar-scaling theory. Jökulhlaup bars are therefore scale invariant and formed in a similar fashion to braid bars in non-jökulhlaup braided rivers. Post-flood fragmentation and reworking of the bars consistently increased the length-width ratio of preserved bar fragments from approximately two and one half to over five. These observations increase our understanding of the preservation potential and final form of jökulhlaup deposits and provide the basis for an improved model for the recognition of jökulhlaup deposits in the geomorphological and sedimentary record. L’apparition d’un dépôt de crue dans l’enregistrement géomorphologique et sédimentaire est à la fois le produit des processus qui fonctionnent lors de la crue, mais également de ceux opérant après l’événement. Ces derniers remanient le dépôt de crue et surimposent à l’archive sédimentaire un enregistrement géomorphologique de processus fluviaux ‘normaux’. Près de la moitié du volume d’eau total engendré par le jökulhlaup du Skeiðarársandur de ...